Alternative policies to combat inflation : proceedings of a conference cosponsored by Centre for the Study of American Business and Federal Reserve Bank of St. Louis (Missouri : Centre for the study of american Business, 1979)
This is the proceedings of a conference cosponsored by Center for the Study of American Business and Federal Reserve Bank of St. Louis, St. Louis, Missouri, on November 28, 1978.
osc 2/11/17
Loans
Keywords: Inflation; Economic history; United States of America